2018
DOI: 10.1530/eje-17-0751
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, prevalence and seasonal onset variation of Addison’s disease among persons with type 1 diabetes mellitus: nationwide, matched cohort studies

Abstract: The risk to develop AD among persons with T1DM is more than 10 times higher than in persons without T1DM. Persons with T1DM develop AD at a younger age. The incidence of AD may have a seasonal pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
(54 reference statements)
1
9
0
Order By: Relevance
“…In our study, Addison disease clustered most often with thyroid ADs in accordance with a recent Swedish nationwide observational cohort study (33). Unlike in another Swedish study (34) where persons with T1D developed Addison disease at a younger age, no association with age at diabetes diagnosis, duration of diabetes, or age was detected in the Finnish cohort.…”
Section: Addison Diseasesupporting
confidence: 91%
“…In our study, Addison disease clustered most often with thyroid ADs in accordance with a recent Swedish nationwide observational cohort study (33). Unlike in another Swedish study (34) where persons with T1D developed Addison disease at a younger age, no association with age at diabetes diagnosis, duration of diabetes, or age was detected in the Finnish cohort.…”
Section: Addison Diseasesupporting
confidence: 91%
“…As a large proportion of patients with type 1 diabetes (T1D), Hashimoto's thyroiditis (HT), Graves' disease (GD), and autoimmune Addison's disease (AD) develop polyautoimmunity or Autoimmune Polyendocrine Syndrome (2)(3)(4)(5), it can be expected that patients with these diseases have similar immunological deviations. Autoantibodies produced by B cells are the most evident immunological feature in patients with T1D, HT, GD and AD, which can directly cause symptoms and modulate the function of other immune cells (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Organ-specific autoantibodies in T1DM endocrine organs, such as systemic lupus erythematosus (SLE), vitiligo, and CD [18,19]. Previous studies have found that 15-30% of T1DM patients have comorbid autoimmune thyroid diseases, 0.97-16.7%, celiac disease; and 0.5-1%, Addison's disease [20], as evidenced by the presence of autoantibodies such as TPOA, TGA, tTGA and 21-OHA. A substantial proportion of T1DM patients seropositive for other organ-specific autoantibodies will progress to a clinical condition more complex and intractable than T1DM alone, so it is critical to identify subclinical comorbidities as early as possible by autoantibody screening [21].…”
Section: Discussionmentioning
confidence: 99%